Female Employment and Intimate Partner Violence: Evidence from Syrian Refugee Inflows to Turkey - Bilge Erten; Pinar Keskin (Institute of Labor Economics (IZA), 2021)
We investigate the impact of female employment on intimate partner violence by exploiting the differential arrivals of Syrian refugees across Turkish provinces as an exogenous labor market shock. By employing a distance-based instrument, we find that refugee inflows caused a decline in female employment with no significant impact on male employment. This decline led to a reduction in intimate partner violence, without changes in partner characteristics, gender attitudes, co-residence patterns, or division of labor. Our results are consistent with instrumental theories of violence: a decline in female earning opportunities reduces the incentives of men to use violence for rent extraction.
Keywords: F22; J12; O15; 330; refugees; forced migration; employment; intimate partner violence